A novel method to evaluate cleaning quality of oil in shale using pyrolysis pyrogram. Issue 5 (21st January 2020) - Dong, Xu; Shen, Luyi; Zhao, Jianpeng; Liu, Xuefeng; Sun, Yuli; Golsanami, Naser; Wang, Fei; Bi, Haisheng; Zitha, Pacelli
Abstract: Complete and thorough core cleaning is a critical prerequisite for the precise measurements of most rock's petrophysical parameters. In shale, the oil cleaning process, aimed to remove the volatile hydrocarbons, is often complicated by the requirement for intact solid organic. Evaluation of shale's cleaning methods needs to take structural integrity of organic matrix into account but neglected in the existing researches. Here, we develop a novel evaluation method using a modified ESH (extended slow heating) pyrolysis cycle, which starts at a lower initial temperature of 150°C for 10 minutes and then slowly increases to 650°C by 10°C/min. Hydrocarbons on the ESH pyrogram were divided into light free hydrocarbon (SA ), FHR (fluid‐like hydrocarbon, SB ), and solid organic matter (SC ). We propose a set of quantitative evaluation criterions comparing the results of pyrograms, for different types of the hydrocarbons, at different cleaning conditions. We showed that a modified pyrogram achieves complete cleaning with SA and SB removed while SC remains almost intact. The modified pyrogram achieves complete removal of FHR in the second stage of pyrogram, while earlier researches often report residual FHR. The introduced method improves the accuracy in the identification of production potential in kerogen‐rich shale reservoirs up to about 3% of the total pore volume. Further, the new approach allows a quantitative assessment for the cleaning quality without altering the sample's organic matrix. Future studies on the petrophysical properties of the hydrocarbon‐bearing reservoir rocks may benefit from the thorough hydrocarbon removal achieved through the modified pyrogram methods proposed in this study. Abstract : We developed a new set of evaluation criterions for the hydrocarbon cleaning of the kerogen‐rich‐prone shale samples. Critical criterions are as follows: (a) Cleaning needs to achieve complete removal of SA and SB while SC remains intact on the ESH pyrogram; (b) cleaning is considered failed if any notable change in SC is reported.